2017
DOI: 10.24875/ric.17002131
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution and Cluster Detection of Childhood Leukemia in the Metropolitan Area of Guadalajara, Mexico

Abstract: Background: Acute leukemia is the most common cancer in childhood. Analyzing the spatial distribution of acute leukemia may generate the identification of risk factors. Objective: To study the incidence rate of acute leukemia, its geographic distribution, and cluster detection in the metropolitan area of Guadalajara, Mexico. Methods: We included children under 15 years of age diagnosed with acute leukemia during the period 2010-2014 in the metropolitan area of Guadalajara. Each case was geo-referenced to stree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…In the present study, 57.9% (2182 patients) of the disease were observed in boys and the sex ratio of males to females was 1.37. These results are consistent with other studies; other studies showed higher incidence of disease in boys than in girls [4,9,[24][25][26]. According to the American Cancer Society's 2019 report, 55 percent of new cases and 56 percent of ALL deaths were boys [27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, 57.9% (2182 patients) of the disease were observed in boys and the sex ratio of males to females was 1.37. These results are consistent with other studies; other studies showed higher incidence of disease in boys than in girls [4,9,[24][25][26]. According to the American Cancer Society's 2019 report, 55 percent of new cases and 56 percent of ALL deaths were boys [27].…”
Section: Discussionsupporting
confidence: 91%
“…The results of spatial pattern analysis showed that ALL in Iran tended to high spatial autocorrelation and spatial clustering and this clustering was more intense for high values of incidence (hot spots). The emergence of clusters in the assessment of the spatial incidence of ALL has been recognized as an amplifying factor for the influence of environmental risk factors, and especially infectious pathogens, on the disease cycle [7,9,[13][14][15][16]. Among the predisposing, enabling and reinforcing factors that lead to occurrence of leukemia, some researchers suspect the role of viruses (HBV, HCV, HCG, and HTLV-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico, no large-scale epidemiologic studies have been conducted in this population, but some studies suggest the incidence of ALL in Mexico is among the highest in the world [16][17][18][19]. The worldwide incidence of ALL varies from 2.0 to 3.5 cases per 100,000 inhabitants per year, whereas in Mexico the incidence is higher than 6/100,000 inhabitants per year [18,20]; the explanation for this difference is unknown. Mexican hematologists were the first to prove that malnutrition is an adverse prognostic factor in children with ALL [21], an observation that has been confirmed worldwide [22].…”
Section: Geographical Differences In Mexicomentioning
confidence: 98%